Enhancing Organizational Effectiveness Through Employee Work Attitude: Dissection of Nigeria’s Hospitality Industry - Edeh, Friday Ogbu; Islam, Mohammad Fakhrul; Egwu, Kevin Chukwuoyims; Irem, Collins Okechukwu; Ssekajugo, Derrick; Oben, Desmond Neji; Olanipekun, Benedict Dayo (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Every business aims to succeed in the competitive environment by injecting various customer attraction and retention mechanisms into the workplace. However, the hospitality sector requires managers to be proactive in delivering prompt services that would motivate them to come back after the first experience. To achieve this objective, employee work attitude behaviour must be considered.  It was this problem that prompted the researchers of this study to examine the predictability of employee work attitude on the effectiveness of hospitality firms operating in Nigeria's work setting. Middle-line managers, supervisors, and low-level employees constitute the sample frame. To avoid bias in selection, simple random was used. Copies of the primary instrument were used to collect data. Frequency distribution was used to analyse respondents’ data while the research propositions were analysed with linear regression with the aid of IBM SPSS statistical software version 25. The finding of the study showed that employee work attitude has a positive significant effect on organisational effectiveness. The study concluded that employee work attitude measured in terms of job satisfaction and job involvement enhances and improves organisational effectiveness of hospitality firms in Nigeria through prompt service delivery and customer satisfaction. The implication of the study is that; supervisors, operations managers, and HR managers should pay positive attention to the attitude of their employees to discourage employee turnover that could lead to customer withdrawal.